Analytical thinking and its relationship to logical intelligence for scientific fifth-grade students in mathematics - et. al., Prof. Hassan Kamel Resan Al-Kinani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify the correlational relationship between analytical thinking and logical intelligence among fifth-grade scientific students in the Directorate of Education in Diwaniyah in mathematics, and in order to verify the goal, the researchers adopted the descriptive approach to conform to the nature of the research, and the following null hypotheses were formulated: 1) There are no statistically significant differences at the level of significance (0.05) between the average true and hypothetical performance of fifth grade students in the Diwaniyah Education Directorate in the analytical thinking test. 2) There are no statistically significant differences at the significance level (0.05) between the mean scores of male and female students in analytical thinking. 3) There are no statistically significant differences at the level of significance (0.05) between the average true and hypothetical performance of the fifth grade students in the Diwaniyah Education Directorate in the logical intelligence test. 4) There are no statistically significant differences at the significance level (0.05) between the mean scores of male and female students in logical intelligence. 5) There is no statistically significant correlation at a significance level (0.05) between analytical thinking and logical intelligence among the fifth scientific students (biological) in the Diwaniyah Education Directorate. 6) There is no statistically significant correlation at a significance level (0.05) between analytical thinking and logical intelligence among students of the fifth scientific (biological) in the Diwaniyah Education Directorate. Then the research community was identified, represented by the scientific (biological) fifth-grade students in the Directorate of Education in Diwaniyah, and the sample was chosen by the stratified random method as it consisted of (400) students and by (176) students and (224) students, and the two research tools were built: the analytical thinking test and the logical intelligence test And application to the sample, then conducting statistical analyzes of the paragraphs of the two tests and making sure of the psychometric properties and using the appropriate statistical tools and statistical package (spss) to analyze the results of the application of the two tests, and the following results were revealed: 1) Fifth-grade students possessing the scientific (biological) in the Diwaniyah Education Directorate for analytical thinking. 2) There is no difference between male and female students in having analytical thinking. 3) Fifth-grade students do not possess science (biological) in the Diwaniyah Education Directorate for Logical Intelligence. 4) There is no difference between male and female students in having logical intelligence. In light of the results of the current research, a number of recommendations and proposals have been drawn up concerning the educational field and the field of scientific research, including: 1) Directing the attention of those in charge of educational institutions in the number of different curricula, which include analytical thinking skills and areas of logical intelligence in mathematics curricula and for all academic levels and not being limited to information only. 2) Conducting similar research on other societies and stages of study to find out the extent of their possession of analytical thinking and logical intelligence, as well as the relationship of analytical thinking with other types of multiple intelligences to know the nature of the relationship and its direction.